Pilot-Plant Testing of Ammoniacal-Cyanidation for Gold Recovery from Copper Gold-Bearing Ore (The Australasian Institute of Mining and Metallurgy, 2010)
Pilot-Plant Testing of Ammoniacal-Cyanidation for Gold Recovery from Copper Gold-Bearing Ore The results of pilot-plant tested ammoniacal-cyanidation of gold recovery from copper gold-bearing ore are presented in this paper. This ore is from a deposit of Russian Federation with gold and copper grade 9.5 g/t and 0.4 per cent, respectively. Copper is largely present as malachite and azurite. The presence of chalcopyrite and bornite is also observed. In order to recover gold, gravity is recommended. Two options of ammoniacal-cyanidation using leaching of gravity tails, CIP and filtration, were tested. It was found that ammoniacal-cyanidation using filtration of leaching tailings and recycled solutions is the most optimal option. The proposed flow sheet provides for 89.7 per cent gold recovery from gravity tailings at the consumption of NaCN 0.9 kg/t and (NH4)2CO3 7.5 - 9 kg/t. Compared to conventional cyanidation, this technology decreases the consumption of sodium cyanide from 4 up to 0.9 kg/t at the same gold recovery. It can be recommended for the treatment of copper gold-bearing ores with the similar composition.